2018
DOI: 10.4067/s0718-95162018005002502
|View full text |Cite
|
Sign up to set email alerts
|

Organic and conventional farming differentially influenced soil respiration, physiology, growth and head quality of artichoke cultivars

Abstract: Soil amendment using organic fertilizer has been used widely to dispose animal waste, reduce environmental pollution and improve soil and fruit quality. The objective of this two-year study was to assess the influence of organic and conventional systems on growth, marketable yield, head quality (chlorogenic acid and cynarin concentration) and soil chemical properties of globe artichoke (Cynara cardunculus). Cultivars used were Deserto, Lulu, Romolo, 11-018, 12-179, Green Globe Improved and Imperial Star. Ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
(48 reference statements)
2
21
1
1
Order By: Relevance
“…On the other hand, the highest WUE, mainly due to high PN, was found in the plants growing with the highest SWRs concentrations, especially in BW treatments, indicating that nutrients from SWRs were invested in photosynthetic capacity. A similar result was found in plants fertilized in saline soils (Leskovar and Othman 2018), and can also be confirmed by the higher chlorophyll content found in these treatments. Looking at the efficiency of the photosystem II, all treatments with SWRS at 0.5% and BW2% showed a good performance in the reduction of the primary electron acceptor from the PSII (Fm was high, particularly compared to WW2%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, the highest WUE, mainly due to high PN, was found in the plants growing with the highest SWRs concentrations, especially in BW treatments, indicating that nutrients from SWRs were invested in photosynthetic capacity. A similar result was found in plants fertilized in saline soils (Leskovar and Othman 2018), and can also be confirmed by the higher chlorophyll content found in these treatments. Looking at the efficiency of the photosystem II, all treatments with SWRS at 0.5% and BW2% showed a good performance in the reduction of the primary electron acceptor from the PSII (Fm was high, particularly compared to WW2%).…”
Section: Discussionsupporting
confidence: 86%
“…Also, methods that increase the water use efficiency should be promoted in order to sustain crop yields (Fließbach et al 2007;Alagöz and Yilmaz 2011). Organic soil amendments or fertilizers, such as agricultural by-products or waste, could be effective solutions (Leskovar and Othman 2018;Truong and Marschner 2018). In Europe, the agricultural sector produces more than 200,000 t per year of coarse wool.…”
Section: Introductionmentioning
confidence: 99%
“…The INM and OM which recorded the highest SBQI values with the highest CO 2 release followed by IC and Control. The present results are in agreement with the previous reports on organic and conventional nutrient management (Leskovar and Othman, 2018).…”
Section: Soil Co 2 Evolution and Its Relation With Soil Biological Atsupporting
confidence: 94%
“…can reduce the half-life times of the herbicide in soil. In our study, we showed that soil preincubation with an organic amendment (inoculated or not) can improve microbial responses to simazine contamination and improve the soil quality (Leskovar and Othman 2018). This preincubation caused an increase in the enzymatic activity and improved the soil conditions in order to obtain better simazine degradation rates and a lower half-life time.…”
Section: Discussionmentioning
confidence: 74%